Love's in sight! Volume 3 - Uoyama (Mangaka) (VIZ Media, LLC, 2023)
Morio Kurokawa is the toughest-looking tough guy around. Yukiko Akaza is a self-possessed girl with a vision impairment attending a school for the blind. The whole city fears Morio, but Yukiko sees the real him--he's a soft sweetheart who's just searching for his place in the world! As Morio and Yukiko continue to grow closer, their friends do too--or try to, at least! Differences in their lived experiences lead to clashes between Morio and Sora, Yukiko's best friend--but could Sora's love of running help them all find common ground and work together to take down a bully? --Amazon